Unveiling the impacts of food security on community health: a scoping review - Mohd. Tohit, Nor Faiza; Mat Ya, Roselawati; Haque, Mainul (Ibn Sina Trust, 2025)
Food security, defined as consistent access to sufficient, safe, and nutritious food, is crucial in shaping community health. This scoping review explores the multidimensional impacts of food security on physical, mental, and social well-being. Malnutrition, stemming from both undernutrition and overnutrition, links food insecurity to health issues such as stunted growth, obesity, and chronic diseases like diabetes and heart conditions. Moreover, the psychological toll of food insecurity is significant, manifesting as stress, anxiety, and depression while exacerbating social inequalities and perpetuating cycles of poverty and ill health.